Influence of the core filler composition on the recovery of alloying elements during the self-shielded flux-cored arc welding - Bogdan Trembach; Aleksandr Grin; Nataliia Makarenko; Serhii Zharikov; Illia Trembach; Oleg Markov (Journal of Materials Research and Technology, 2020)
Introduction of the exothermic mixture into the flux-cored electrode core filler and its’ influence to the deposited metal composition and recovery factors of alloying elements were investigated in the article. An influence of FCAW-S core filler composition with exothermal mixture implemented for recovery hardfacing by wear-resistant alloys was investigated in this article. An influence of oxidizing agent to reducing agent ratio (CuO/Al) in the composition of exothermic mixture, on the recovery factors of the alloying system components was considered. As well as the ratio of exothermic mixture oxidizing agent to graphite (CuO/C) and the amount of exothermic mixture (TM) in the flux-cored wire filler composition. Some mathematical models of the recovery factors dependence on the studied factors were received as a result of the investigation.An analysis of the results of the study showed that the ratio of the oxidizing agent to the reducing agent in the exothermic mixture (CuO/Al) had the greatest influence on the recovery factors of alloying elements. Received mathematical dependences of the alloying elements recovery rates allowed to optimize the calculation of composition of the FCAW-S core filler mixture with exothermic mixture and the deposited metal composition. To receive the high values of the elements recovery factors, the parameters subject to investigation should have the following values:CuO/C = 3.75 … 5.25, CuO/Al = 3.75 … 5.25, CuO + Al = 33 … 45 wt.%.